How Can We Better Comprehend the Disposition of Elementary School Students towards Advanced Mathematical Thinking? - Nadya Dewinda Agustin; Mohamad Syarif Sumantri; Arita Marini (Journal of Education Reseach and Evaluation, 2024)
Conventional mathematics teaching methods emphasize speed and accuracy, creating unnecessary pressure and often inaccurately measuring children's achievements. This research aims to build a framework, systematically examine students' affective areas, especially mathematical dispositions, and analyze the urgency of Advanced Mathematical Thinking (AMT). This research is a comprehensive investigative or exploratory mixed methods research using data triangulation. The subjects involved in this research were 80 elementary school students. The data collection method used was a questionnaire. In addition, this study combined open-ended questions and random narratives that captured participants' perspectives on mathematics learning. The data analysis technique uses qualitative and quantitative descriptive analysis. The research results show that teachers must consider students' various cognitive, emotional and psychomotor capacities and constraints during the educational process. This can be done using appropriate learning activities and methodologies, such as individual assignments and exploratory learning that adapt to students' abilities.    Additionally, using narrative-based summative assessments can be an appropriate approach for educators to identify and analyze the specific needs of their students. This research implies the importance of considering students' psychological and emotional factors in designing effective mathematics learning strategies.